Praca gruntowego wymiennika ciepła na tle zmiennych warunków atmosferycznych = The efficiency of the ground-coupled heat exchanger under varying weather conditions - Pązik, Rafał; Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article we present the work of the ground-coupled heat exchanger working in the systems with heat recovery. Efficiency of work under varying weather conditions, including winter and summer were analyzed. We also present the results of the temperature and comfort after a year-long operation.
Keywords: gruntowy wymiennik ciepła; rekuperacja; wentylacja; chłodzenie pasywne; GŻWC; ground-coupled heat exchanger; recuperation; ventilation; passive cooling; GHE